Uptake of and intention to use oral pre-exposure prophylaxis for HIV among pregnant and post-natal women in Eswatini: a cross-sectional survey - Khumalo, Philisiwe Ntombenhle; Mkhonta, Siphiwesihle Sibonisiwe; Kindandi, Kikanda; Matse, Sindy; Dlamini, Phinda Brian; Tukei, Vincent; Machekano, Rhoderick; Woelk, Godfrey (Frontiers in Reproductive Health, 2023)
Introduction In Eswatini, HIV incidence among women of childbearing age is 1.45%. Eswatini introduced oral pre-exposure prophylaxis (PrEP) for HIV prevention in 2016 and requires that all HIV-negative pregnant and post-natal women (PPW) visiting health care facilities be offered PrEP. Methods Between September-November 2021, we conducted a survey among HIV-negative PPW from 16 purposively selected healthcare facilities in the Hhohho and Shiselweni regions in Eswatini. We interviewed consenting HIV-negative PPW using a structured questionnaire to collect data on PrEP knowledge, attitudes, intentions, and practices, as well as information on partner HIV status and stigma. Multivariate logistic regression was used to determine predictors of PrEP use and intention, adjusted for significant covariates. Results Of 1,484 PPW women approached, 1,149 consented and were interviewed, of whom 704 (61.3%) were post-partum and 445 (38.7%) pregnant. The median age was 25 years [Interquartile Range (IQR) = 21–30 years], with 533 (46.4%) 18–24 years old. Among the 1,149 women, 930 (80.7%) had ever heard about PrEP; 635 (55.3%) had knowledge about PrEP; 183 (15.9%) were currently using PrEP; and 285 (24.8%) had ever used PrEP. Increased odds of PrEP use were associated having HIV-positive male partner (aOR:7.76, 95%CI 3.53- 17.04); positive attitudes to PrEP (aOR:1.56, 95%CI: 1.02–2.40); and high self-efficacy (aOR:1.49, 95%CI:1.13–1.98). Among 864 women who never used PrEP, 569 (65.3%) intended to use PrEP in the future. Odds of intention to use PrEP were higher among women with low levels of education (aOR:2.23, 95% CI: 1.32–3.77); who ever heard about PrEP (aOR:1.69, 95%CI: 1.12–2.56); and had high self-efficacy (aOR:1.57, 95%CI: 1.31–1.87). Regarding stigma, among all women, 759 (66%) either agreed or strongly agreed that people would think they have HIV if they were to use PrEP; 658 (57.3%) reported they would be labelled as having multiple sex partners; 468 (40.7%) reported that their partner would think they are having risky sex with other people. Of 102 women who had discontinued PrEP, a majority stopped due to side effects 32 (35.2%). Conclusion Only about 50% of women had knowledge of PrEP, and PrEP uptake among PPW was low, though intention to use appeared high. More efforts to reduce stigma and promote PrEP use, including adequate information on side effects, are needed.